MEMBUMIKAN PENDIDIKAN MODERASI BERAGAMA DALAM REPRESENTASI TOKOH PUNAKAWAN CERITA WAYANG LAKON SEMAR MBANGUN KAHYANGAN - Prabowo, Dimas Setiaji; Sulistianingsih, Irka; Widodo, Agung (Universitas Islam Lamongan, 2024)
The emergence of intolerant ideologies, the circulation of many hoax news, the emergence of acts of violence that triggered divisions due to the lack of literacy regarding the religious moderation education are the background for this research. This research will attempt to explain how religious moderation education is delivered by the Punakawan wayang in the puppet show intitled Semar Mbangun Kahyangan staged by Dalang Ki Seno Nugroho. This research is classified as qualitative research. The data in this research are in the form of conversations containing religious moderation education from the Punakawan wayang characters in the wayang story Semar Mbangun Kahyangan. Listening techniques and note-taking techniques are the means of collecting data in this research. This research was analyzed using Norman Fairclough's critical discourse analysis. After conducting an in-depth search, it was found that there are seven (7) principles of religious moderation which are part of the religious moderation education contained in the conversations of the Punokawan puppets in the puppet play Semar Mbangun Kahyangan which was staged by Dalang Ki Seno Nugroho. The seven principles were include Tahadhdhur, I'tidal, Musawah, Shura, Al Ishlah, Al Muwathanah, and Tawazun.